2011
DOI: 10.1002/chem.201003628
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Redox‐Active, Intramolecular Charge‐Transfer Chromophores by the [2+2] Cycloaddition of Ethynylated 2H‐Cyclohepta[b]furan‐2‐ones with Tetracyanoethylene

Abstract: Ethynylated 2H-cyclohepta[b]furan-2-ones 5-15 have been prepared by Pd-catalyzed alkynylation of 3-iodo-5-isopropyl-2H-cyclohepta[b]furan-2-one (2) with the corresponding ethynylarenes or the reaction of 2-iodothiophene with 3-ethynyl-5-isopropyl-2H-cyclohepta[b]furan-2-one (4) under Sonogashira-Hagihara conditions. Compounds 5-15 reacted with tetracyanoethylene in a formal [2+2] cycloaddition reaction, followed by ring opening of the initially formed [2+2] cycloadducts, cyclobutenes, to afford the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 77 publications
0
37
0
1
Order By: Relevance
“…We have reported the synthesis of redox-active chromophores 15 with the aim of the creation of stabilized electrochromic materials. 17 As a part of this study, we have also reported 2H-cyclohepta [b]furan-2-one-substituted TCBDs 13 and azulenesubstituted TCBDs 10 and DCNQs 11 , in which we identified some novel hybrid structures of violenes and cyanines 18 with the redox 20 activities. Bis(2H-cyclohepta [b]furan-2-one-substituted) and bis(azulene-substituted) TCBDs, which exhibit reversible color changes during the electrochemical reaction, are successful examples of an extension for the violene-violene hybrid structure.…”
Section: Electrochemistrymentioning
confidence: 94%
See 3 more Smart Citations
“…We have reported the synthesis of redox-active chromophores 15 with the aim of the creation of stabilized electrochromic materials. 17 As a part of this study, we have also reported 2H-cyclohepta [b]furan-2-one-substituted TCBDs 13 and azulenesubstituted TCBDs 10 and DCNQs 11 , in which we identified some novel hybrid structures of violenes and cyanines 18 with the redox 20 activities. Bis(2H-cyclohepta [b]furan-2-one-substituted) and bis(azulene-substituted) TCBDs, which exhibit reversible color changes during the electrochemical reaction, are successful examples of an extension for the violene-violene hybrid structure.…”
Section: Electrochemistrymentioning
confidence: 94%
“…The shift value of 10 (27 nm) is larger than that of the corresponding TCNE-adduct of 1 (6 nm). 13 These results are assumed that the first excited-state has a larger dipole moment 35 compared with that in the ground state, due to the effective ICT character from 2H-cyclohepta [b]furan-2-one to the DCNQ unit.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…5 Although its unusual reactivity has already been revealed by many research groups, 6 there are few 2H-cyclohepta [b]furan-2-one derivatives for the application to the advanced materials with potentially useful electronic properties. For the extension of this chemistry, we have focused our studies on the synthesis of tetracyanobutadiene (TCBD) 7 and dicyanoquinodimethane (DCNQ) 8 derivatives of 2H-cyclohepta[b]furan-2-one by the formal [2+2] cycloaddition-cycloreversion reaction of the corresponding alkyne derivatives with tetracyanoethylene (TCNE) and 7,7,8,8- The electronic properties of the new compounds obtained by this reaction were characterized by CV, DPV, and absorption spectroscopy. In addition one of the DDQ-adducts was revealed the molecular structure by X-ray crystallographic analysis.…”
Section: Introductionmentioning
confidence: 99%